Pengaruh Overconvidence Bias terhadap Pengambilan Keputusan Investasi di Pasar Saham Selama Perang Rusia-Ukraina - Irawan, Rini Larasati (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study examines the impact of overconfidence bias on investment decision-making during the Rusia-Ikraine war in the Indonesian energy stock market. Overconfidence bias is a cognitive bias where investors overestimate their ability to predict market movements, often leading to an increase in transaction frequency and the taking of irrational risks. Using stock return data from the companies INCO, ADRO, ITMG, and the JKSE during the 2022-2024 activity lever segregation methods to explore this phenomenon. The results indicate that high market volatility exerbates overconfidence bias, particulary among investors with high activity levels leading to more frequent transactions and suboptimal investment decisions. In contrast, investors with lower activity levels tend to exhibit more rational behavior, maintaining better portolio stability during extreme market conditions promote more rational decision-making. These findings contribute sifnificantly to the understanding of investor psychology the importance of strategies to mitigate cognitive biases, especially during periods of high market volatility.